High Altitude Illness among Rapidly Ascending Pilgrims to Kailash Mansarovar - Baniya, Santosh; Lama, Tai Anjuk (Journal of Nepal Health Research Council, 2023)
Background: High altitude pilgrims typically ascend rapidly, are not well prepared for the austere environment and tend to have multiple co-morbidities. Here, we list the trend of altitude and other illnesses who visited Humla district hospital (2,950 meters) following very rapid ascent to Kailash Mansarovar (4,500 meters). Methods: A prospective study was conducted among 55 patients at the Humla District Hospital from September 2019 – August 2022. Patients who fell ill during pilgrimage and brought to the hospital were included. The patients were assessed with medical history and clinical examination. Lake Louise Score Acute Mountain Sickness Score (2018) was used for the diagnosis of Acute Mountain Sickness. Results: A total of 56 evacuees visited the hospital which included 55 patients and 1 brought dead. The mean age was 50.63 ± 10.91 years. Sixteen patients (29.1%) developed symptoms within 24 hours and 15 patients (27.3%) within 48 hours of ascent. Headache 42 (76.4%) was the most common complain. Mild acute mountain sickness (30.9%; 17 patients) was the most common altitude related illness while 14 patients (25.4%) were diagnosed with non-altitude related illnesses. Twelve patients (21.8%) had co-morbidities like hypertension and diabetes mellitus. Conclusions: In the rapidly ascending pilgrims, majority of travelers requiring medical attention are suffering from some form of altitude illnesses. Hence, proper planning and public awareness about slow and gradual ascent profile is necessary to make the travel safer. Keywords: High altitude illnesses; high altitude pilgrimage; kailash mansarovar; rapid ascent.